2003
DOI: 10.1128/aem.69.6.3280-3287.2003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Biosurfactant-Producing Bacteria in Undisturbed and Contaminated Arid Southwestern Soils

Abstract: Biosurfactants are a unique class of compounds that have been shown to have a variety of potential applications in the remediation of organic-and metal-contaminated sites, in the enhanced transport of bacteria, in enhanced oil recovery, as cosmetic additives, and in biological control. However, little is known about the distribution of biosurfactant-producing bacteria in the environment. The goal of this study was to determine how common culturable surfactant-producing bacteria are in undisturbed and contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
178
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(198 citation statements)
references
References 61 publications
15
178
1
4
Order By: Relevance
“…Amiriyan et al (2004) reported 11 biosurfactant producers from Iranian oil reservoirs. The present findings are in accordance with the findings of Bodour et al (2003) and Amiriyan et al (2004). However, findings of Ramesh et al (2010) was contrary from this study who reported biosurfactant only in hydrocarbon contaminated soil.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Amiriyan et al (2004) reported 11 biosurfactant producers from Iranian oil reservoirs. The present findings are in accordance with the findings of Bodour et al (2003) and Amiriyan et al (2004). However, findings of Ramesh et al (2010) was contrary from this study who reported biosurfactant only in hydrocarbon contaminated soil.…”
Section: Discussionsupporting
confidence: 94%
“…A total of seven biosurfactant producing isolates were obtained from soil and oil samples. Bodour et al (2003) obtained 45 biosurfactant producing isolates from hydrocarbon contaminated South Western soils of Arizona and most of the surfactant producing isolates was tending from contaminated and co-contaminated soil. Amiriyan et al (2004) reported 11 biosurfactant producers from Iranian oil reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, different microbial genera synthesize structurally different classes of biosurfactants whereas strains belonging to a same species produce structurally similar biosurfactants. However, small differences in the molecular structures can have major impact on the functions and potential industrial applications of biosurfactants (Bodour et al, 2003).…”
Section: Introductionmentioning
confidence: 99%